Mixed-ligand metal complexes containing an ONS Schiff base and imidazole/benzimidazole ligands: synthesis, characterization, crystallography and biological activity - Mazlan, Nurul Ain; S. A. Ravoof, Thahira Begum; Tiekink, Edward R. T.; Mohamed Tahir, Mohamed Ibrahim; Veerakumarasivam, Abhi; Crouse, Karen Anne (Springer, 2014)
Salicylaldehyde-4-methylthiosemicarbazone (H2MTSali) has been prepared via the condensation reaction of 4-methyl-3-thiosemicarbazide and salicylaldehyde. Four new mixed-ligand copper(II) and nickel(II) complexes with a general formula [M(MTSali)L] (M = Cu2+ or Ni2+; L = co-ligand) were synthesized, where L is either imidazole (im) or benzimidazole (bzim). The Schiff base and its mixed-ligand complexes were characterized by IR and UV/Vis spectroscopy, and the complexes by molar conductivity and magnetic susceptibility measurements. The spectroscopic data indicated that the Schiff base behaves as a tridentate ONS donor ligand coordinating via the phenoxide-oxygen, azomethine-nitrogen, and thiolate-sulphur atoms. Magnetic data indicate a square planar environment for the nickel(II) complexes while molar conductance values indicate that the metal complexes are essentially non-electrolytes in DMSO solution. X-ray crystallography shows Cu(MTSali)bzim (1) and Ni(MTSali)bzim (3) to be isostructural, with the metal(II) ions being coordinated by a N2OS donor set that defines an approximate square planar geometry; in both cases, the benzimidazole is splayed with respect to the coordination plane. The copper(II) complexes were active against MDA-MB-231 and MCF-7 breast cancer cell lines, more so than H2MTSali, whereas the nickel(II) complexes were inactive.